Digital repository at Nanyang Technological University : implementing a subject metadata scheme - Sam, Lena Choon Foong. (2009)
One information service that has emerged in libraries with the advancement of digital technologies is the online institutional repository. DR-NTU is the digital institutional repository jointly developed by NTU Library and the Wee Kim Wee School of Communication and Information, using open source software DSpace from MIT, to facilitate the capture, storage and preservation of the intellectual output of the NTU community.